Expressing the category of value relationship at the phonetic level - Isakova Zilolakhon Zokirovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In the structure of speech, the value relationship is mainly revealed through units of phonetic, lexical and grammatical level and paralinguistic means. In speech segment and suprasegment phonetic units are used together and show the value feature, in grammar the value relationship is expressed through morpheme, word, phrase, sentence, and at the lexical level value is stated through the word and its meanings. In real speech the most part of value relation usually occurs by units of phonetic level.